PENENTUAN RUTE OPTIMAL UNTUK MEMINIMALISIR BIAYA PENGIRIMAN DENGAN METODE SAVING MATRIX DAN NEAREST NEIGHBOR DI PT BAKPIA KURNIA SARI - Arif Prasetyo; Ayudyah Eka Apsari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
PT Bakpia Kurnia Sari is one of the producers of bakpia, a traditional food from Yogyakarta. The purpose of this research is to address the problem of high distribution costs in delivering bakpia from the production site to each outlet. Based on data processing, the results show a reduction in total distance from the initial 116 km to 88.6 km using the Saving Matrix method and to 74.7 km using the Nearest Neighbor method, with the proposed routes consisting of 2 routes serving 9 outlets. After determining the new optimal route sequences, the initial monthly distribution cost of IDR 11,438,800 was reduced to IDR 7,900,600 using the Saving Matrix method and to IDR 7,562,600 using the Nearest Neighbor method.